Budget impact analysis of two treatment approaches for hepatitis C in Malaysia through the use of voluntary and compulsory licensing options - Azzeri, Amirah; Dahlui, Maznah; Mohamed, Rosmawati; McDonald, Scott Alexander; Jaafar, Hafiz; Shabaruddin, Fatiha Hana (Frontiers in Public Health, 2023)
A scaled-up treatment cascade with direct-acting antiviral(DAA) therapy is necessary to achieve global WHO targets for hepatitis C virus(HCV) elimination in Malaysia. Recently, limited access to Sofosbuvir/Daclatasvir(SOF/DAC) is available through compulsory licensing, with access to Sofosbuvir/Velpatasvir(SOF/VEL) expected through voluntary licensing due to recent agreements. SOF/VEL has superior clinical outcomes but higher drug acquisition costs than SOF/DAC. A stratified treatment cascade might be the most cost-efficient approach for Malaysia whereby all HCV patients are treated with SOF/DAC except for patients with cirrhosis who are treated with SOF/VEL. This study aimed to conduct a five-year budget impact analysis of the proposed stratified treatment cascade for HCV treatment in Malaysia. A disease progression model that was developed based on model-predicted HCV epidemiology data was used for the analysis, where all HCV patients in scenario A were treated with SOF/DAC for all disease stages. In contrast, in scenario B, SOF/DAC was used only for non-cirrhotic patients and SOF/VEL was used for cirrhotic patients. Healthcare costs associated with DAA therapy and disease stage monitoring were included to estimate the downstream cost implications. The stratified treatment cascade within Scenario B was found to be cost-saving compared to Scenario A. The cumulative savings for the stratified treatment cascade was USD 1.4 million over 5 years. A stratified treatment cascade with SOF/VEL was expected to be cost-saving and can result in a budget impact reduction in overall healthcare expenditure in Malaysia.